Sentinel node biopsy in the breast cancer: Possibility of the avoidance of axillary node dissection - Golubović Andrija; Stojiljković Bratislav T.; Plzak Aleksandar; Radovanović Zoran D.; Patrnogić Aleksandar (Archive of Oncology, 2002)
(Conclusion) This researching, and many others, indicates that in certain patients (especially T1a and T1b), under precise criteria, when SN metastases are not present, axillary dissection in the breast cancer (10, 22) and all its consequences (lymphoedeama, numbness, pain, limited movement in the shoulder joint) could be avoided. We should remember that nowadays at least 50% of women undergo axillary nodes dissection within the breast cancer operative treatment because of histopathologically negative nodes.